A complex wireless sensors model (CWSM) for real time monitoring of dam temperature. Issue 2 (February 2023) - Afzal, Jamil; Yihong, Zhou; Afzal, Usama; Aslam, Muhammad
Abstract: The following work is based on real-time temperature monitoring during the construction and during the operation of a dam. For this purpose, we have proposed a sensing model named: the "complex wireless sensors model (CWSM)" for measuring the value of different factors like temperature, humidity and pressure on the dam. The installation of the proposed model has been discussed with its wireless networking. The model contains five types of sensors i.e. humidity, temperature, pressure, sun and irradiance sensors for measuring the variation of different factors. The computation modeling of CWSM has been discussed in the paper. 3-D Finite Element method is used for thermal analysis. As the result, it is concluded that the wireless network will be more suitable for measuring and analyzing the effects of temperature, humidity, water pressure and solar radiation on the dam.